Hydrogen Bond Acceptor Propensity of Different Fluorine Atom Types: An Analysis of Experimentally and Computationally Derived Parameters. Issue 34 (27th May 2021) - Vulpetti, Anna; Dalvit, Claudio
Abstract: The propensity of organic fluorine acting as a weak hydrogen bond acceptor (HBA) in intermolecular and intramolecular interactions has been the subject of many experimental and theoretical studies often reaching different conclusions. Over the last few years, new and stronger evidences have emerged for the direct involvement of fluorine in weak hydrogen bond (HB) formation. However, not all the fluorine atom types can act as weak HBA. In this work, the differential HBA propensity of various types of fluorine atoms was analyzed with a particular emphasis for the different types of alkyl fluorides. This was carried out by evaluating ab initio computed parameters, experimental 19 F NMR chemical shifts and small molecule crystallographic structures (extracted from the CSD database). According to this analysis, shielded (with reference to the 19 F NMR chemical shift) alkyl mono‐fluorinated motifs display the highest HBA propensity in agreement with solution studies. Although much weaker than other well‐characterized HB complexes, the fragile HBs formed by these fluorinated motifs have important implications for the chemical‐physical and structural properties of the molecules, chemical reactions, and protein–ligand recognition. Abstract : Ab initio computed parameters and experimental 19 F NMR chemical shifts are used to assess the differential hydrogen bond acceptor propensity of various types of fluorine atoms with a particular emphasis for the different types of alkyl fluorides. Although weak, the hydrogen bond complexes formed by organic fluorine have important implications.